The operational approach to and challenges of high-technology clinical simulation in South Africa - R van Wyk; M Labuschagne; G Joubert (South African Medical Association, 2023)
Background. Research has been published on the application of high-technology clinical simulation as a training tool in South Africa (SA). However, littlehas been published on the operational approach taken and challenges faced when establishing and running a high-technology clinical simulation facility.Objective. To ascertain the current operational approach taken and challenges faced regarding high-technology clinical simulation by SA simulation facilities.Methods. A quantitative descriptive study with an online questionnaire survey was conducted with representatives of simulation facilities at SA publichealth professions training institutions where high-technology simulation is used. The questionnaire consisted of sections dealing with the characteristics ofand challenges faced by the facilities and the following operational aspects: management, funding, staffing and staff development, curriculum integration,physical environment and research.Results. Forty-two institutions were approached and 23 (54.8%) participated. Simulation was used at 16 (69.6%) of these institutions, representing17 facilities, with 14 (82.4%) using high-technology simulation. Nine (64.3%) of the 14 simulation facilities were custom built. Four (28.6%) facilitieshad dedicated technical staff. The participating simulation facilities acquired their funding mainly through institutional budget allocations (78.6%) andgovernment education grants (78.6%). The number of students using high-technology simulation facilities was the highest among the fifth-year (median195) and sixth-year (median 21) students.Conclusion. Large student groups and a lack of trained simulation staff are some of the challenges being faced by high-technology simulation facilities in SA.Recommendations and guidelines should be established to ensure effective integration and alleviation of all operational aspects and challenges